Impact of ursodeoxycholic acid therapy in autoimmune liver disease patients with COVID-19 and its clinical prognosis - Minghui Li; Weihua Cao; Tingting Jiang; Wen Deng; Shiyu Wang; Shuling Wu; Lu Zhang; Yao Lu; Min Chang; Ruyu Liu; Xiaoyan Ding; Ge Shen; et al. (Elsevier, 2024)
To explore the impact of ursodeoxycholic acid (UDCA) on severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and clinical outcomes in patients with autoimmune liver disease (AILD). Patients diagnosed with AILD were enrolled and divided into a UDCA group and a non-UDCA group based on whether they received UDCA treatment. Relevant data were collected regarding AILD diagnosis, treatment, biochemical indicators, and imaging examination. The incidence of SARS-CoV-2 infection and the prognosis of AILD patients were observed. A total of 1,138 patients completed follow-up. The usage rate of hormone (P = 0.003) and immunosuppressant (P = 0.001) used for treating AILD in the non-UDCA group was markedly lower than in the UDCA group. The UDCA usage rate was markedly lower in SARS-CoV-2 infected patients than in uninfected patients (P = 0.003). The rate of SARS-CoV-2 infection in the non-UDCA group was significantly higher than in the UDCA group (P = 0.018). Logistic regression analysis showed that UDCA use (P = 0.003) was correlated to a lower incidence of SARS-CoV-2, while immunosuppressant use (P = 0.017) increased the incidence. Recovery time from SARS-CoV-2 infection was markedly longer for those receiving UDCA treatment than those in the non-UDCA group (P = 0.018). UDCA is associated with low SARS-CoV-2 incidence in AILD patients, while immunosuppressant increases its incidence instead. Patients receiving UDCA treatment have a longer recovery time after being infected.